2018
DOI: 10.3727/108354217x15143857878714
|View full text |Cite
|
Sign up to set email alerts
|

Air Quality and Inbound Tourism in China

Abstract: The issue of air quality in China has gotten great attention worldwide. This study makes the first effort to investigate the impact of air pollution on China's inbound tourism, using panel data at city level and the technique of corrected least square dummy variable (CLSDV). This study demonstrates how air pollution in China adversely impacts inbound tourism demand as well as the lagged effect of air pollution. Furthermore, this study reveals that for cities with different degrees of air pollution, the impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 12 publications
2
28
0
Order By: Relevance
“…ere are two parts to evaluate the energy consumption for tourism activities, which are transportation-related tourism activities and destination-related tourism activities, respectively [19,26], and both illustrate how the tourism affects the air environment. e negative effects on the air environment from tourism have been discussed in the areas worldwide, from developed countries such as Spain [27] to developing ones such as China [28] based on grounded theory, questionnaires, etc.…”
Section: E Effects Of Tourism On Air Environmentmentioning
confidence: 99%
“…ere are two parts to evaluate the energy consumption for tourism activities, which are transportation-related tourism activities and destination-related tourism activities, respectively [19,26], and both illustrate how the tourism affects the air environment. e negative effects on the air environment from tourism have been discussed in the areas worldwide, from developed countries such as Spain [27] to developing ones such as China [28] based on grounded theory, questionnaires, etc.…”
Section: E Effects Of Tourism On Air Environmentmentioning
confidence: 99%
“…A set of studies have quantitatively revealed the harm of local air pollution to inbound tourism in China. The studies included Becken et al [24], Deng et al [26], Dong et al [27], Tang et al [17], Xu and Reed [28], Xu et al [29], Zhou et al [30], and Zhou et al [31] on different districts in Mainland China; Cheung and Law [32] and Law and Cheung [33] on the Hong Kong SAR of China; and Chen et al [34] on the Sun Moon Lake scenic area in the Taiwan Province of China.…”
Section: Impact Of Air Pollution In Chinamentioning
confidence: 99%
“…Although there were uncertainties associated with the remote sensing measurements (for example, affected by weather and the precision of the electrical instruments), the accuracy and reliability of the PM 2.5 grids data have been highly appreciated. In fact, both data sources have been widely utilized in previous research (e.g., [8,9,11,12,42]). The data from the two data sources were highly correlated.…”
Section: Datamentioning
confidence: 99%